World populationand production : trends and outlook - Woytinsky W.S; Woytinsky E.S (New York : The Twentieth Century Fund, 1953)
This book provides a detailed economic history of world-wide problems such as man and its environment, world needs, agriculture, energy and mining etc
Includes bibliographical references and index
kjo 15/01/2019
Loans
Keywords: E.S. Woytinsky; Economic history; Population; Natural resources